(untitled) (Journal of the College of Education for Women, 2019)
The aim of this research is to show the importance of the effective useof the internet in academic libraries; to improve the services and to increasethe competence of librarians.The research has given some recommendations to improve the qualityof services and the need for cooperative network among academic libraries.